THE AFFECT OF STRATEGIC HUMAN RESOURCE MANAGEMENT ON EMPLOYEES PERFORMANCE - Altaher , Asmahan; AlShaikhly, Nooraldeen A. (International Journal of Psychosocial Rehabilitation, 2020)
Strategic human resource management (SHRM) practices are used by large foreign multinational companies to improve their performance. The study aimed to investigate the effect of strategic human resource management practices on employees’ performance: in Jordanian pharmaceuticals Companies. The study population consisted of two Jordanian largest Companies. Questionnaire was developed to collect data from employees. Statistical techniques were used to test the study hypotheses. The result showed that the Jordanian pharmaceuticals factor is has the most effect on employee performance.The researcher recommend that companies need to improve their strategic human resource management, in order to build a strong SHRM system. The researcher recommends that companies should provide their employees more fair incentives system Companies have to be more aware of their employee opinions by having a policy to motivate their lower-level employee. Finally the relationship between SHRM practices and firm performance is indirect through motivation.